Implementation of Digital Marketing Strategy and Preparation of Financial Reports for Oti Snack & Catering UMKM in Cimahi City - Rizki Indrawan (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
The Small and Medium Enterprises (MSME) sector has survived the Covid-19 outbreak that has ravaged Indonesia in the last two years, including Cimahi, West Java. MSME actors were impacted by the loss of consumers; many decided to discontinue operations, financial reports were hampered, and people's purchasing power was drastically reduced. The impact causes the business to be devoid of buyers as a result of the social distancing policy, which forces everyone to confine themselves to their homes. This has undoubtedly impacted the Cimahi City MSME sector. Oti Snack & Catering, for example, is a food-related SME. Students in this UNJANI KKN program help MSME sector business actors survive this pandemic and for a long time by assisting in improving product quality, good product packaging, utilizing digital marketing through social media as a sales strategy, and utilizing digital accounting to make it easier for business actors to record and report financially.